KEBIJAKAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PERTAMBANGAN DAN PENGARUHNYA TERHADAP KESEJAHTERAAN MASYARAKAT (Studi Kasus pada Desa Koeono, Kecamatan Palangga Selatan, Kabupaten Konawe Selatan) - La Ode Muhammad Elwan; Irfan Ido; La Ode Alwi; Hendrik Wanda P (Journal Publicuho, 2018)
ABSTRACTResearch has been conducted which aims to find out how the Corporate Social Responsibility (CSR) Policy of Mining and Its Influence on Community Welfare in Koeono Village, South Palangga Subdistrict of South Konawe Regency. The data used in this research is qualitative. Determination of the number of samples taken from 110 head of household with an error rate of 5%, so gets 87 respondents. The variables used in this research are CSR fund transfer mechanism, target accuracy, community involvement in CSR program planning implementation, CSR value transparency, transaction cost and monitoring and community welfare.The results of the analysis show that the mining CSR program simultaneously has an influence on the welfare of the community. Partially, however, only CSR fund transfer mechanism variables affect the level of community welfare, while the accuracy of targets, community involvement in the implementation of CSR program planning, CSR value transparency, transaction costs and supervision does not affect the level of community welfare. Based on the determinant coefficient of percentage of influence of CSR policy on mining where CSR fund transfer mechanism, target accuracy, community involvement in CSR program implementation, transparency of CSR value, transaction cost and supervision on community welfare of Koeono Village, South Palangga Subdistrict of South Konawe Regency is 34.4 %, the remaining 65.6% influenced by other variables not examined in this research.